STATUS SOSIAL EKONOMI KELUARGA PEMILIK SAWAH PASCAPENAMBANGAN EMAS DI JORONG KOTO PANJANG NAGARI LIMO KOTO KECAMATAN KOTO VII KABUPATEN SIJUNJUNG - Sari, Melta Ardilla; Abbas, Ardi; Rahmad, Darmairal (Pendidikan Sosiologi, 2013)
The background of this research by the field which is used as a gold mine eyes so that the transition from peasant society to pencharian penamabang gold so that the economy and lead to increased consumptive lifestyle while rice is used as a gold mine that has been damaged by gold reserves are depleted while society is still running so implications for the socio- economic status of the family owners pascapenambagan gold fields . This research uses descriptive qualitative research . The type of data is the primary data and secondary data . Methods of data collection is done in two ways : ( 1 ) observation , ( 2 ) interviews . Analysis of the data used by the model of interactive data analysis ( Milles and Huberman ) . The results pascapenamabangan Jorong gold in Koto Panjang tilled fields that have been left alone out into the swamp and sand . Socioeconomic status of the family owners pascapenambangan gold fields in terms of educational informant merely elementary , junior high and high school , work informants as housewives , artisans ojeg , farm laborers and workers of gold mining . while revenue declined informants and people involved including gold mining investors , operators , foremen , and laborers